All that glitters is Golden Mile Complex - Ho, Francine Pei Ying (Nanyang Technological University, 2023)
As Golden Mile Complex approaches its golden jubilee, long-term tenants, residents and patrons, unfortunately, will have to commemorate this milestone with goodbyes. Following a collective sale of the mixed-use development, affectionately known as "Little Thailand", Golden Mile Complex will begin redevelopment this May. Our project follows the communities that will be uprooted and dispersed all over the country. We also aim to capture the landmark's significance in the lives of the people affected.